Beyond Branding: Naming Rights As Public-Private Synergy In Jakarta Mrt’s Marketing Strategy (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This article analyzes the implementation of marketing government in the naming rights scheme of Jakarta MRT stations as an innovative strategy for financing public services. This study used a qualitative case study approach through observation, interviews, and social media metadata analysis. Findings indicate that Jakarta MRT has systematically implemented six stages of t marketing government, from product design to message delivery, to achieve synergy between commercial objectives and public service. Analysis reveals public engagement in responding to partner brands, station locations, and consumption activities, reflecting both acceptance and critical attitudes toward the commercialization of public space. Although the marketing government strategy is generally considered successful, challenges remain in balancing commercial visibility with participatory and social values. This study emphasizes the importance of continuous evaluation in marketing government practices to strengthen the legitimacy and effectiveness of sustainable public services.
Keywords: Marketing Government; Naming Rights; Innovation; Public Transport; MRT Jakarta